Application and Progress of Raman Spectroscopy in Male Reproductive System - Zhang, Feng; Tan, Yiling; Ding, Jinli; Cao, Dishuang; Gong, Yanan; Zhang, Yan; Yang, Jing; Yin, Tailang (Frontiers in Cell and Developmental Biology, 2022)
Raman spectroscopy is a fast-developing, unmarked, non-invasive, non-destructive technique which allows for real-time scanning and sampling of biological samples in situ, reflecting the subtle biochemical composition alterations of tissues and cells through the variations of spectra. It has great potential to identify pathological tissue and provide intraoperative assistance in clinic. Raman spectroscopy has made many exciting achievements in the study of male reproductive system. In this review, we summarized literatures about the application and progress of Raman spectroscopy in male reproductive system from PubMed and Ovid databases, using MeSH terms associated to Raman spectroscopy, prostate, testis, seminal plasma and sperm. The existing challenges and development opportunities were also discussed and prospected.